Answer:
[tex]V=\dfrac{PT}{m}\ ln\dfrac{M+m}{M}-gT[/tex]
Explanation:
Given that
Constant rate of leak =R
Mass at time T ,m=RT
At any time t
The mass = Rt
So the total mass in downward direction=(M+Rt)
Now force equation
(M+Rt) a =P- (M+Rt) g
[tex]a=\dfrac{P}{M+Rt}-g[/tex]
We know that
[tex]a=\dfrac{dV}{dt}[/tex]
[tex]\dfrac{dV}{dt}=\dfrac{P}{M+Rt}-g[/tex]
[tex]\int_{0}^{V}V=\int_0^T \left(\dfrac{P}{M+Rt}-g\right)dt[/tex]
[tex]V=\dfrac{P}{R}\ ln\dfrac{M+RT}{M}-gT[/tex]
[tex]V=\dfrac{PT}{m}\ ln\dfrac{M+m}{M}-gT[/tex]
This is the velocity of bucket at the instance when it become empty.